Emprego de ultrassom para a oxidação e separação de compostos orgânicos sulfurados em hidrocarbonetos e determinação de enxofre por técnicas espectrométricas e cromatográficas - Duarte, Fábio Andrei (2009)
In this work, a process based on ultrasonic energy for sulfur removal from petroleum fractions was proposed. The process combines ultrasonic energy and a peroxyacid reagent in order to achieve the required sulfur content recommended by current regulations for fuels. Studies for ultrasound-assisted oxidative (UAOD) procedure were performed in a hydrocarbon fraction obtained from petroleum distillation and dibenzothiophene was used as model sulfur compound. Parameters for UAOD procedure as ultrasonic irradiation time, ultrasonic amplitude, oxidizing reagents amount, kind of acid and the solvent for extraction step were investigated. Sulfur removal was about 95% after only 9 min of ultrasonic irradiation (20 kHz, 750 W, 40% of amplitude) using H2O2 and acetic acid, followed by extraction with methanol, with oil recovery higher than 95%. The proposed process using ultrasound allows higher removal efficiency in comparison with the experiments performed under the same conditions, however using mechanical stirring. The quantification and identification of sulfur compounds, performed in order to establish the removal efficiency as well as to evaluate the products obtained by UAOD process, were carried out using both spectrometric and chromatographic techniques. Inductively coupled plasma optical emission spectrometry, ultraviolet fluorescence and gas chromatography (equipped with pulsed flame photometric detector and mass spectrometry) were used for total sulfur and sulfur compounds determination. In general, the proposed process needs low reagents consumption and it can be performed in less time than conventional procedures, without the necessity of high temperature and pressure or metallic catalysts.